An Analysis of Imperative Sentences in English Travel Brochures: A Study of Ammar International Travel - Adinda Ramadhani; Rani Mahraini; Muhammad Hatta Siregar; Dewi Nurmala (Westscience Press, 2026)
Travel brochures use different types of sentences to attract and guide readers. One of the most common types is the imperative sentence, which is used to give instructions, make suggestions, and invite readers to take action. This study examines the use of imperative sentences in the English travel brochures of Ammar International Travel, a travel agency based in Medan, Indonesia. The aims of this study are to identify the types of imperative sentences used, determine the most dominant type, and explain their functions in the brochures. This study uses a qualitative descriptive method following Creswell (2018). The classification of imperative sentences is based on Quirk et al. (1985), who divide them into three types: directive, persuasive, and invitational. The data were taken from five English brochures published between 2023 and 2025. A total of 31 imperative sentences were identified. The findings show that persuasive imperatives are the most dominant (48.39%), followed by invitational imperatives (29.03%) and directive imperatives (22.58%). Each type has a different function: directive imperatives give instructions, persuasive imperatives highlight benefits and encourage customers, and invitational imperatives create a friendly and engaging tone. These results indicate that imperative sentences play an important role in making travel brochures both informative and persuasive.